Therapeutic potential of adipose-derived stem cells and macrophages for ischemic skeletal muscle repair - Rybalko, Viktoriya (Regen Med, 2017)
AIM: Progressive ischemia due to peripheral artery disease causes muscle damage and reduced strength of the lower extremities. Autologous cell therapy is an attractive treatment to restore perfusion and improve muscle function. Adipose-derived stem cells (ASCs) have therapeutic potential in tissue repair, including polarizing effects on macrophages (MPs). MATERIALS & METHODS: Co-culture systems of ASCs and MPs were analyzed for gene and protein expression modifications in ASC-conditioned MPs. Co-transplantation of MPs/ASCs in vivo led to improved skeletal muscle regeneration in a mouse model of peripheral artery disease. RESULTS: ASCs/MPs therapy restored muscle function, increased perfusion and reduced inflammatory infiltrate. CONCLUSION: Combined MPs/ASCs cell therapy is a promising approach to restore muscle function and stimulate local angiogenesis in the ischemic limb.